Controlling soil-transmitted helminthiasis in pre-school-age children through preventive chemotherapy. - Marco Albonico; Henrietta Allen; Lester Chitsulo; Dirk Engels; Albis-Francesco Gabrielli; Lorenzo Savioli (PLoS Neglected Tropical Diseases)
Pre-school age children account for 10%-20% of the 2 billion people worldwide who are infected with soil-transmitted helminths (STHs): Ascaris lumbricoides (roundworm), Trichuris trichiura (whipworm), and Ancylostoma duodenale/Necator americanus (hookworms). Through a systematic review of the published literature and using information collated at World Health Organization headquarters, this paper summarizes the available evidence to support the recommendation that pre-school children should be included in regular deworming programmes. The first section describes the burden of STH disease in this age group, followed by a summary of how infection impacts iron status, growth, vitamin A status, and cognitive development and how STHs may exacerbate other high mortality infections. The second section explores the safety of the drugs themselves, given alone or co-administered, drug efficacy, and the importance of safe administration. The third section provides country-based evidence to demonstrate improved health outcomes after STH treatment. The final section provides country experiences in scaling up coverage of pre-school children by using other large scale public health interventions, including vitamin A programmes, immunization campaigns, and Child Health days. The paper concludes with a number of open research questions and a summary of some of the operational challenges that still need to be addressed.